لێكه‌وته‌ كۆمه‌ڵايه‌تييه‌كانى هه‌واڵى ساخته‌ لەسەر کۆمەڵگە - حسێن, هەتاو حەمەساڵح; محمد, پەروین أبوبکر; عارف, شیلان علی (Sulaimani Journal for Humanities, 2021)
This research is an attempt to clarify the impact of Media on society. Obviously, there is a lot of news in unusual times; in the meantime, the possibility of infiltrating fake news is increasing. New media and especially social media are considered as effective tools for disseminating that news all over the world. The aim of this study is to determine the social implications of this news on the society. The researchers studied the effects of the fake news published on social media, by sharing research questionnaires which was published in Google Form. 407 peoples filled out the form. Data was collected between March and April 1 that was, during the quarantine period caused by the spread of the (Corona/Covid 19) in the Kurdistan Region. The results showed that the fake news had a negative impact on society and created an unhealthy atmosphere and a lot of anxiety for peoples.